Public Participation Model in Policy Formulation: Case Study of Job Creation Act Number 11/2020 - Paramita, Rastri; Sanapiah, Aziz; Taufik, M.; ., Hamka (Journal of Ecohumanism, 2025)
Constitutional Court Decision No. 91/PUU-XVIII/2020 demonstrates how politicians and the community define public involvement differently. These differences include disagreements on the types of public participation channels used, the meaning of openness in legal discussions, and public access limitations to Bill documents and Academic Papers on Job Creation in 2020. This article investigates the causes of disparities in understanding public engagement and potential solutions. Using normative legal research, we found that three factors influence differences in the meaning of public participation between policymakers and the community: differences in the need for forms of participation, a lack of agreement on the types of actors who can be involved, and weakness in parliament’s representation system. The solution to this challenge is to create a framework for public engagement, particularly during the legislative process. This public engagement framework must be tailored to Indonesia’s political culture. It must be diversified, conceptually broad, and flexible, allowing for critical thinking and revealing the aspects and factors that define this phenomenon. This framework may also handle the many configurations of elements in participatory processes.